Mass Gathering Sport Events and the Spread of Viral Respiratory Infection: Japanese Professional Baseball and Influenza. (June 2023) - Funahashi, Hiroaki; Cardazzi, Alexander; Watanabe, Nicholas Masafumi
Using weekly-level influenza case data from all 47 prefectures in Japan alongside data from Nippon Professional Baseball (NPB) league from 1999 to 2018, we examine the effect of hosting games on local influenza transmission. The results highlight that during the flu season, for every NPB game held at its home ballpark, there is an average increase of 0.18 cases per sentinel medical institution (SMI) between that week and the following week. The effects are robust to different specifications and placebo tests. This translates to about a 0.1% increase in the number of cases during the overlap of NPB and flu seasons.